Beyond Close Reading: Integrating the Comparative Literary Method and Pedagogy in Enhancing Literature Education in the Philippines - Alerta, Honeylet L. (Philippine Humanities Review, 2022)
The unforeseen pandemic that struck the world in 2020 has destabilized the established systems of the global economy, technology, medical healthcare, and the academe. People from around the globe have suffered, displaced, and disoriented in varying degrees. This dilemma has increased demand and prioritized the job market and access to healthcare. Strengthening the digital world to accommodate the basic needs of humanity has been given focus to enable survival in the core of education – the disciplines of the humanities. Even before the pandemic, the discipline of comparative literature has had ongoing debates about its interdisciplinarity, its framework, and method as a mode of inquiry, and its pedagogy in relation to teaching world literature. With the COVID-19 pandemic, the compelling issues of the discipline resurface as another layer of challenge to literature teachers: engaging the students to read and examine literary texts not just through close reading, but with eye for parity in an online distance learning setup. This essay seeks to showcase how, for now, the only comparative literature program in the country offered at the Department of English and Comparative Literature (DECL) of the University of the Philippines Diliman can be integrated in enhancing literature teaching in universities and classrooms in the Philippines. More importantly, this paper proposes ways to streamline the program in making up for the Philippine comparative literary studies through its method and pedagogy despite the current limitations brought by the pandemic.